Effects of Poe And Poe-G-Ma on impact and tensile properties of polyamide nanocomposites - Othman, N.; Rahmat, A. R.; Hassan, A.; Wahit, M. U. (2005)
The incorporation of nanoclay in polyamide 6 (PA6) may increase the strength and water resistance of hygroscopic PA6. However impact strength of PA6 was reduced upon the addition of nanoclay. Blends of polyamide 6 nanocomposites (PA6NC) with either unmodified polyethylene octene elastomer (POE) or reactive polyethylene octene elastomer grafted with maleic anhydride (POE-g-MA) were prepared to overcome the brittleness. The blends were prepared using co-rotating twin screw extruder followed by injection molding into tests samples. The results show that the impact strength of PA6NC containing POE-g-MA is significantly higher than samples containing POE. The plausible reason is that of the better compatibility between PA with POE-g-MA compared to POE with PA6 due to formation of POE-g-PA6 copolymer during the melt processing. POE-g-MA also caused in higher tensile strength values compared to when POE is used. The SEM study show that the rubbery disperse phase is smaller when POE-g-MA is used, making it more effective as impact modifier.